Mercury speciation in soils and attic dust in the Idrija area - Gosar, Mateja; Šajn, Robert; Biester, Harald (Geologija, 2002)
Speciation of mercury in soils and attic dust in Idrija and its surroundings was studied by means of pyrolysis technique. The results show that soil and attic dust have similar course of Hg release. The samples show double peak curves with first maximum between 200 °C and 250 °C and a second one between 250 and 350 °C. The first peak (200-250 °C) indicates non-cinnabar Hg compounds. Compared to the standard Hg compounds curves and that of humic acid bound Hg of the forest soil sample, it is most reasonable that this peak represents Hg bound or sorbed to matrix components. The second peak, which occurs in the higher temperature range, indicates the presence of cinnabar. In areas close to the mine or tailings Hg occurs predominantly as cinnabar. In more distant areas, Hg is mainly bound to matrix components.